La division du sujet selon Saint Paul: Поделеноста на субјектот според Свети Павле - Riha, Rado; Popovska, Elisaveta (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Rado Riha | Радо Риха Title (French): La division du sujet selon Saint Paul Title (Macedonian): Поделеноста на субјектот според Свети Павле Translated by (French to Macedonian): Elisaveta Popovska | Елисавета Поповска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 59-71 Page Count: 12 Citation (French): Rado Riha, “La division du sujet selon Saint Paul,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 59-71. Citation (Macedonian): Радо Риха, „Поделеноста на субјектот според Свети Павле“, превод од француски Елисавета Поповска, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 59-71.